Atuação fonoaudiológica em pacientes queimados: uma proposta clínica - Toledo, Paula Nunes (2001)
This work intends to approach the performance of spech technical specialist oral moving in 20 burned patients of face and neck, of the Bumed Clinic and Reparative Surgery of the Municipal Hospital Dr. Carmino Caricchio, with segment in the national health c1inic of specialties. We developed a study capable to cover the field of action speech therapeutic, for this, we already left of the roads traveled by the medicine, for the -':., physiotherapy and for the occupational therapy. , We verified the course of speech technical specialist oral moving and we based this research on the observation ofthe alterations ofthe functions ofthe oral system and of the component structures of this system, caused by the sequels of the bum. The patients were appraised and the techniques developed in the therapeutic process and applied the individuaIs of this research, for 3 months, they are good to demonstrate the contribution that Fonoaudiologia renders in the bumed patients' of face rehabilitation and neck